Implementation of Interactive Powerpoint Learning Media on Students' Creative Thinking Skills - Aisyatul Jannah; Shokhibul Arifin; Asrori (Lafadz Jaya Publisher, 2023)
This study aims to determine how interactive PowerPoint learning media can improve students' creative thinking skills at SDN 2 Bulus Tulungagung. Using a qualitative approach and descriptive analysis, the study involved 11 grade 6 students. The results showed that the use of interactive PowerPoint media effectively enhanced students' creative thinking skills, as seen from the indicators of fluency, flexibility, originality, and detail. Students who were previously less active in conventional learning exhibited increased motivation and participation after using this media. The use of this media also contributed to creating a more engaging and enjoyable learning environment, which motivated students to be more enthusiastic in participating. Based on these findings, it can be concluded that interactive PowerPoint media is effective in supporting the development of students' creative thinking skills and can be used as an innovative alternative learning tool in primary education.